2023
DOI: 10.3847/1538-3881/acda91
|View full text |Cite
|
Sign up to set email alerts
|

Keck Planet Imager and Characterizer Emission Spectroscopy of WASP-33b

Abstract: We present Keck Planet Imager and Characterizer (KPIC) high-resolution (R ∼35,000) K-band thermal emission spectroscopy of the ultrahot Jupiter WASP-33b. The use of KPIC’s single-mode fibers greatly improves both blaze and line-spread stabilities relative to slit spectrographs, enhancing the cross-correlation detection strength. We retrieve the dayside emission spectrum with a nested-sampling pipeline, which fits for orbital parameters, the atmospheric pressure–temperature profile, and the molecular abundances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 93 publications
3
20
0
Order By: Relevance
“…The data extraction is identical to that described in Finnerty et al (2023b), which differs slightly from the current version of the supported KPIC DRP. 14 HIP 95771 (spectral type M0.5IIIb) was used for wavelength calibration at the start of the night.…”
Section: Data Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data extraction is identical to that described in Finnerty et al (2023b), which differs slightly from the current version of the supported KPIC DRP. 14 HIP 95771 (spectral type M0.5IIIb) was used for wavelength calibration at the start of the night.…”
Section: Data Reductionmentioning
confidence: 99%
“…A new SVD is then performed on the component-injected forward model in order to replicate the distortion of the planet signal from projecting these components out, similar to Line et al (2021). In contrast with Finnerty et al (2023b), we do not negatively inject the forward model prior to removal of the SVD components, which significantly speeds the log-likelihood calculation. This choice makes a stronger assumption that repeating the SVD on the component-injected model accurately reproduces the distortion of the observed planet signal, but has proven successful in previous work (e.g., Line et al 2021).…”
Section: Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not find TiO in the real data, which means that the true value of the VMR of TiO at the terminator of WASP-33b is even lower and is much lower than expected from the chemical equilibrium calculations. Even in the presence of high-altitude clouds, the upper limit derived from the injection-recovery tests is lower than the VMR of TiO expected for WASP-33b with its high metallicity (2-15 × solar; Finnerty et al 2023). Overall, the possibility of TiO not being detected at the terminator owing to the presence of high-altitude clouds and/or the influence of H − (corresponding to P cloud = 10 −2 bar) can be roughly ruled out.…”
Section: Nondetection Of Tiomentioning
confidence: 72%
“…Several studies have found evidence of a temperature inversion in its dayside atmosphere (e.g., Haynes et al 2015;Nugroho et al 2017;Cont et al 2021). Species such as Si I, Fe I, Ti I, Ti II, V I, OH, CO, H 2 O, and TiO have been detected in the dayside atmosphere by highresolution emission spectroscopy (Nugroho et al 2020;Cont et al 2021;Nugroho et al 2021;Serindag et al 2021;Cont et al 2022aCont et al , 2022bHerman et al 2022;van Sluijs et al 2023;Finnerty et al 2023). In contrast, studies of the terminator atmosphere have lagged behind due to contamination from stellar pulsations.…”
Section: Introductionmentioning
confidence: 99%